CATCH (Cortisol Apta WATCH): 'Bio-mimic alarm' to track Anxiety, Stress, Immunity in human sweat. (10th September 2021) - Pali, Madhavi; Jagannath, Badrinath; Lin, Kai-Chun; Upasham, Sayali; Sankhalab, Devangsingh; Upashama, Sayali; Muthukumar, Sriram; Prasad, Shalini
Abstract: This work demonstrates an electrochemical label-free cortisol aptasensor (C ortisol A pta-Watch (CATCH) for detection of cortisol from passively perspired eccrine sweat. The platform is designed to track cortisol levels in sweat to understand the implications of stress in different physiological processes of the body. The sensor platform is characterized with zeta potential, FTIR, and electrochemical measurements to understand the aptamer binding chemistry and cortisol binding sensitivity. Following this, the platform's sensitivity to cortisol analyte concentration in human sweat is evaluated using impedimetric and chronoamperometric methods. The results highlight the platform's sensitivity to cortisol with a detection limit of ~1 ng/mL in human sweat and a dynamic range of 1–256 ng/mL.  The performance metrics highlight the ability of the sensor to sensitively detect cortisol in human sweat with high significance ( p <0.05). These studies are demonstrated across triplicate measurements and have low RSD values ( ˷ <2%). The performance was also evaluated on five healthy subjects, indicating the ability to detect sweat cortisol in real time and on-body. Additionally, the developed sensing platform demonstrated excellent correlation with state-of-art reference method with a Pearson's correlation of r  = 0.97 in nine human subject samples. The sensor also demonstrated that the circadian behavior of cortisol can be tracked with elevated levels in the morning and low levels in the evening in a cohort of healthy subjects. The developed aptamer-based cortisol sensing technology can aid in real-time, continuous monitoring facilitating personalized health monitoring.